Bifidobacterium bifidum ATCC 15696 and Bifidobacterium breve 24b Metabolic Interaction Based on 2′- O -Fucosyl-Lactose Studied in Steady-State Cultures in a Freter-Style Chemostat - Manuela Centanni; Scott Ferguson; Ian M. Sims; Ambarish Biswas; Gerald W. Tannock (2019)
Infants fed breast milk harbor a gut microbiota in which bifidobacteria are generally predominant. The metabolic interactions of bifidobacterial species need investigation because they may offer insight into the colonization of the gut in early life. Bifidobacterium bifidum ATCC 15696 hydrolyzes 2'-O-fucosyl-lactose (2FL; a major fucosylated human milk oligosaccharide) but does not use fucose released into the culture medium. However, fucose is a growth substrate for Bifidobacterium breve 24b, and both strains utilize lactose for growth. The provision of fucose and lactose by B. bifidum (the donor) allowing the growth of B. breve (the beneficiary) conforms to the concept of syntrophy, but both strains will compete for lactose to multiply. To determine the metabolic impact of this syntrophic/competitive relationship on the donor, the transcriptomes of B. bifidum were determined and compared in steady-state monoculture and coculture using transcriptome sequencing (RNA-seq) and reverse transcription-quantitative PCR (RT-qPCR). B. bifidum genes upregulated in coculture included those encoding alpha-l-fucosidase and carbohydrate transporters and those involved in energy production and conversion. B. bifidum abundance was the same in coculture as in monoculture, but B. breve dominated the coculture numerically. Cocultures during steady-state growth in 2FL medium produced mostly acetate with little lactate (acetate:lactate molar ratio, 8:1) compared to that in monobatch cultures containing lactose (2:1), which reflected the maintenance of steady-state cells in log-phase growth. Darwinian competition is an implicit feature of bacterial communities, but syntrophy is a phenomenon putatively based on cooperation. Our results suggest that the regulation of syntrophy, in addition to competition, may shape bacterial communities.IMPORTANCE This study addresses the microbiology and function of a natural ecosystem (the infant bowel) using in vitro experimentation with bacterial cultures maintained under controlled growth and environmental conditions. We studied the growth of bifidobacteria whose nutrition centered on the hydrolysis of a human milk oligosaccharide. The results revealed responses relating to metabolism occurring in a Bifidobacterium bifidum strain when it provided nutrients that allowed the growth of Bifidobacterium breve, and so discovered biochemical features of these bifidobacteria in relation to metabolic interaction in the shared environment. These kinds of experiments are essential in developing concepts of bifidobacterial ecology that relate to the development of the gut microbiota in early life.